Prophylactic use of recombinant ADAMTS-13 during pregnancy for congenital thrombotic thrombocytopenic purpura - Éloïse Colliou; Agnès Ribes; Clotilde Gaible; Mathilde Marlas; David Ribes; Isabelle Labadens; Paul Guerby; Stanislas Faguer (Research and Practice in Thrombosis and Haemostasis)
Background: Congenital thrombotic thrombocytopenic purpura (cTTP) related to ADAMTS-13 deficiency is associated with a maternal risk of death of 10% and a risk of fetal loss greater than 50% without treatment. Key Clinical Question: Is prophylactic use of recombinant (r)ADAMTS-13 during pregnancy in patients with cTTP safe and effective in preventing cTTP relapse? Clinical Approach: rADAMTS-13 was given intravenously weekly (40 Units/kg) from 17 weeks’ gestation. ADAMTS-13 activity was undetectable before the first administration, reached 60% to 90% of normal levels 2 hours after, and became undetectable between days 4 and 6. A full dose was given in the hours preceding the delivery and on day 3. No flare-up of cTTP occurred during the pregnancy, and rADAMTS-13 was tolerated well. No anti–ADAMTS-13 antibodies developed. Conclusion: Prophylactic use of rADAMTS-13 during pregnancy may prevent relapse of cTTP and reduce the risk of fetal loss, but an optimal regimen requires further attention.